Police Efforts in Revealing Criminal Acts of Online Fraud - Lalu Hedwin Hanggara; Boy Nurdin (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Crimes caused by the development and progress of Information Technology and Telecommunications are crimes related to the internet, or in foreign terms it is often called cybercrime. Cybercrime is a crime that takes advantage of technological developments, especially the internet. The internet, which presents cyberspace with its virtual reality, offers various hopes and conveniences, but behind that, problems arise in the form of a crime called cybercrime, both the computer network system itself and the computer itself which is the vehicle for committing crimes. There are a variety of digital scams such as phishing, lottery scams, video scams, identity theft and scareware. This study uses a normative juridical approach. The normative juridical approach is legal research carried out by examining literature or secondary data as the basic material to be examined by conducting a search of regulations and literature related to the problem under study. The efforts of the police in handling fraud cases online are guided by the Criminal Procedure Code (KUHAP) as well as in the Regulation of the Indonesian National Police Number 6 of 2019), namely as "Investigators and Investigators". The step taken by the Police is to trace the accounts used by the perpetrators of crimes, where the last whereabouts or position of the perpetrators of these crimes are.